Pemberdayaan Ekonomi Kreatif: Diversifikasi Produk Ayam Olahan di Tanah Sareal, Bogor - Maya D Dyah Maharani; Tatan Sukwika; Dem Vi Sara; Boedhi Oetojo; Arina Rubyasih (Universitas Mathla'ul Anwar Banten, 2021)
EMPOWERING CREATIVE ECONOMY: DIVERSIFICATION OF PROCESSED CHICKEN PRODUCTS IN TANAH SAREAL, BOGOR. The demand for food of animal origin (PAH) is increasing rapidly in Bogor. The demand dominated by broiler products from the Pondokrumput chicken shelter and slaughter facility (TPnA), Tanah Sareal. The TPnA business unit is located in densely populated settlements and sometimes causes social, economic and environmental problems. There is a negative perspective on the neglect of the TPnA business unit in community involvement so that it has negative implications for the existence of the business unit. One of the efforts to reduce its negative impact is to invite the community around TpnA to participate in the processing of TpnA's fresh chicken production into the advanced processed chicken, among others by using the